Cooperative control method strategy for autonomous roundabout - Yuxin Niu (Journal of Highway and Transportation Research and Development)
With the development of intelligent transportation system, the cooperative control of vehicles at intersections has become an important issue worthy of attention. However, existing research mainly focuses on conventional signalized intersections, autonomous roundabouts remain understudied and lack personalized right-of-way allocation solutions. Considering the above problems, this paper proposes a cooperative control method of autonomous vehicles at roundabout based on token ring, which maps virtual tokens to physical lanes and dynamically encodes spatio-temporal access rights, thus achieving conflict-free operation of vehicles at intersections and more equitable right-of-way allocation. The simulation results demonstrate that the proposed method can significantly improve the vehicle traffic efficiency under large traffic flow.